1983
DOI: 10.1001/archderm.119.12.975
|View full text |Cite
|
Sign up to set email alerts
|

PUVA treatment of alopecia areata

Abstract: Twenty-three patients with alopecia areata were treated with photochemotherapy combining oral or topical methoxsalen and UV-A irradiation of the scalp or of the whole body. Eleven of 17 patients with multiple plaques of alopecia areata, alopecia totalis, and alopecia universalis, who were treated with oral methoxsalen and total body irradiation, had complete or more than 90% hair regrowth. Three patients had a relapse. The mean energy required was 505 joules/sq cm. In six cases, topical applications of methoxs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 0 publications
2
18
0
1
Order By: Relevance
“…Photochemotherapy with all types of PUVA (oral or topical psoralen, local or whole body UVA irradiation) claim success rates of up to 60–65% for alopecia areata in uncontrolled studies 175177 , but results are inconsistent. Retrospective reviews reported low response rates 178 or response similar to natural course of the disease 179 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Photochemotherapy with all types of PUVA (oral or topical psoralen, local or whole body UVA irradiation) claim success rates of up to 60–65% for alopecia areata in uncontrolled studies 175177 , but results are inconsistent. Retrospective reviews reported low response rates 178 or response similar to natural course of the disease 179 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…There have been several uncontrolled studies of PUVA treatment for AA, using all types of PUVA (oral or topical psoralen, local or whole body UVA irradiation [15,16,17]), claiming success rates of up to 60–65%. Two retrospective reviews have reported low response rates [18] or suggested that the response was no better than the natural course of the disease [19], although these observations were also uncontrolled.…”
Section: Introductionmentioning
confidence: 99%
“…PUVA therapy has been advocated for severe AA [10, 11, 12, 13]. Its use is based on the concept that the peribulbar and perifollicular mononuclear cell infiltrates may play a direct pathogenic role and that PUVA therapy may eradicate this inflammatory cell infiltrate [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Regarding various background factors, such as age, sex, duration of the disease or time from start of AA to PUVA treatment, there are different conclusions from different studies [4, 11, 12, 13, 14, 15]. According to Healy and Rogers [11]and Mitchell and Douglass [15], the age at the time of the treatment was the most significant parameter which correlated with efficacy of PUVA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation